Synthesis, characterization and adsorption properties of molecularly imprinted silica gel for the removal of 2-hydroxybenzoic acid (2-ha) from aqueous solution / Siti Farhana Bt Abdul Raof - Siti Farhana, Abdul Raof (2014)
A molecularly-imprinted silica gel (MISG) sorbent for selective removal of 2-hydroxybenzoic acid (2-HA) was prepared by a surface imprinting technique with a sol gel process. The 2-HA-imprinted silica sorbent was evaluated by parameters including influence of pH, static, kinetic adsorption and selectivity experiments. The optimum pH for maximum adsorption capacity to the 2-HA appeared around pH 2 by the polymer. Also, the imprinted sorbent has a fast uptake kinetics which is obtained within a short shaking period of 5 min. When the initial concentration of 2-HA solution increases from 20 ppm to 400 ppm, the adsorbed amount of 2-HA increases from 8.57 mg/g to 60.95 mg/g. The polymer displays good selectivity, and exhibit good reusability. Equilibrium isotherms have been measured experimentally for the adsorption of 2-HA towards MISG. Freundlich model is fitted well for the description for 2-HA adsorption towards sorbent. The process was spontaneous in nature. Pseudo second-order model provide the best correlation coefficient for adsorption kinetics 2-HA towards MISG sorbent. The thermodynamics parameters such as ΔG°, ΔH° and ΔS° values indicated that adsorption of 2-HA towards silica gel was feasible, spontaneous and exothermic in the temperature range of 298K to 353K.